2020
DOI: 10.1371/journal.pone.0227454
|View full text |Cite
|
Sign up to set email alerts
|

Key necroptotic proteins are required for Smac mimetic-mediated sensitization of cholangiocarcinoma cells to TNF-α and chemotherapeutic gemcitabine-induced necroptosis

Abstract: Cholangiocarcinoma (CCA), a malignant tumor originating in the biliary tract, is well known to be associated with adverse clinical outcomes and high mortality rates due to the lack of effective therapy. Evasion of apoptosis is considered a key contributor to therapeutic success and chemotherapy resistance in CCA, highlighting the need for novel therapeutic strategies. In this study, we demonstrated that the induction of necroptosis, a novel regulated form of necrosis, could potentially serve as a novel therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…Only two studies have investigated the efficacy of different drugs in limiting CCA development by inducing necroptosis in CCA cell lines. Akara-amornthum et al demonstrated that treatment with both TNFα and a Smac mimetic induced RIPK1/RIPK3/MLKL-dependent necroptosis when caspase was blocked, evidenced by an increased expression of RIPK3 and MLKL in CCA cell lines after treatment [122]. They also proved that the administration of a Smac mimetic could sensitize CCA cells to a low dose of standard chemotherapy with gemcitabine, by increasing TNFα mRNA levels and reversing gemcitabine-induced cell cycle arrest, leading to CD [122].…”
Section: Necroptosis-based Therapies For Cholangiocarcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Only two studies have investigated the efficacy of different drugs in limiting CCA development by inducing necroptosis in CCA cell lines. Akara-amornthum et al demonstrated that treatment with both TNFα and a Smac mimetic induced RIPK1/RIPK3/MLKL-dependent necroptosis when caspase was blocked, evidenced by an increased expression of RIPK3 and MLKL in CCA cell lines after treatment [122]. They also proved that the administration of a Smac mimetic could sensitize CCA cells to a low dose of standard chemotherapy with gemcitabine, by increasing TNFα mRNA levels and reversing gemcitabine-induced cell cycle arrest, leading to CD [122].…”
Section: Necroptosis-based Therapies For Cholangiocarcinomamentioning
confidence: 99%
“…A widely adopted approach for killing cancer cells is to activate apoptosis, and evasion from this type of CD is considered a key step to therapeutic failure and chemotherapy resistance in CCA [122], as reported above. A switch to a non-apoptotic CD, such as necroptosis, can function as a backup system in apoptosis-resistant cells, so antitumor drugs inducing non-apoptotic CD are now considered a new approach for overcoming such a big obstacle in CCA treatment [0].…”
Section: Necroptosis-based Therapies For Cholangiocarcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Second mitochondria-derived activator of caspase (Smac) is a mitochondrial protein that inhibits cellular inhibitors of apoptotic proteins if released into the cytosol, leading to activation of apoptotic caspases, activation of RIP1K, and initiation of apoptosis (39). When caspase activity is inhibited, as occurs in certain infections or tumor cells, Smac and Smac mimetics promote necroptosis (40)(41)(42). We tested whether the Smac mimetic CUDC-427 induced necroptosis of AMs in the presence of the pancaspase inhibitor Z-VAD-FMK (SZ).…”
Section: Resultsmentioning
confidence: 99%
“…Necroptosis has been reported to enhance anti-tumor immunity in colon cancer and melanoma [ 41 , 42 ] and RIPK3 expression status is proposed to influence the clinical outcome of TLR3-based cancer immunotherapy [ 45 ]. The loss of key necroptotic proteins in cancers has become a major hindrance for necroptosis-based therapy [ 73 , 74 ] but results of our recent studies in CCA patients demonstrated that RIPK3 and MLKL were both expressed in a great majority of CCA patients, allowing for the possible development of necroptosis-based therapeutic approaches [ 75 ]. Collectively, these results provide a potential for development of a novel therapeutic approach targeting TLR3 by TLR3 ligands in combination with Smac mimetic that can trigger both apoptosis and necroptosis in a RIPK1-dependent manner.…”
Section: Discussionmentioning
confidence: 99%